Effectiveness of passiflora stint associated with conventional treatment of patients with hypertension - Caridad Jacas García; Elizabet Polanco Machado; Luis Ernesto Pelegrín Monpie; Lilia Rosa Rodríguez García; Maricel Hechavarría Torres (Centro Provincial de Información de Ciencias Médicas, 2017)
A therapeutic intervention to evaluate the effectiveness of using passiflora stint associated with the conventional treatment in 20 patients suffering from essential hypertension, who were assisted in a family doctor's office of Manzanillo Granma, was carried out from October, 2014 to April, 2015. The population was distributed in 2 groups: study and control. The first group was prescribed with passiflora stint combined with conventional medicines, according to associated diseases and personal risks, the second group received conventional medical treatment with the same requirements. An evaluation was carried out after 15 and 30 days to 6 months. There was a prevalence of sixty years and over patients (35.0%) and female sex. The treatment was effective in 42 members of the study group (70.0%) and 27 members of the control group (45.6). It was concluded that passiflora stint associated with conventional treatment was effective to control tension numbers.